Vascular Extracellular Superoxide Dismutase Activity in Patients With Coronary Artery Disease: Relation to Endothelium-Dependent Vasodilation - Landmesser, Ulf; Merten, Roland; Spiekermann, Stephan; Büttner, Karsten; Drexler, Helmut; Hornig, Burkhard (Circulation (New York, N.Y.), 2000)
Background —Increased inactivation of nitric oxide by oxygen free radicals contributes to endothelial dysfunction in patients with coronary artery disease (CAD). We therefore determined the activity of extracellular superoxide dismutase (EC-SOD), the major antioxidant enzyme system of the vessel wall, and its relation to flow-dependent, endothelium-mediated dilation (FDD) in patients with CAD. Methods and Results —SOD isoenzyme activity was determined in coronary arteries from 10 patients with CAD and 10 control subjects. In addition, endothelium-bound EC-SOD activity (eEC-SOD), released by heparin bolus injection, and FDD of the radial artery were measured in 35 patients with CAD and 15 control subjects. FDD, determined by high-resolution ultrasound, was assessed at baseline, after intra-arterial infusion of vitamin C, N -monomethyl- l -arginine, and combination of both. EC-SOD activity in coronary arteries (control subjects: 126±14; CAD: 63±11 U/mg protein; P <0.01) and eEC-SOD activity in vivo (control subjects: 14.5±1.1; CAD: 3.8±1.1 U · mL −1 · min −1 ; P <0.01) were reduced in patients with CAD. Activity of eEC-SOD was positively correlated with FDD ( r =0.47; P <0.01) and negatively with the effect of the antioxidant vitamin C on FDD ( r =−0.59; P <0.01). In young individuals with hypercholesterolemia, however, eEC-SOD activity was increased (21.0±1.2 U · mL −1 · min −1 ; n=10; P <0.05). Conclusions —In patients with CAD, vascular EC-SOD activity is substantially reduced. The close relation between endothelium-bound EC-SOD activity and FDD suggests that reduced EC-SOD activity contributes to endothelial dysfunction in patients with CAD. In young hypercholesterolemic individuals, however, endothelium-bound EC-SOD activity is increased and may, in part, counteract impairment of endothelial function as the result of increased formation of oxygen free radicals.